Information Technology in Public Health Aspects: A Literature Review - Meiryani,; Wong, Heri Sukendar; Murtedjo,; Pamungkas, Hanggoro (International Journal of Psychosocial Rehabilitation, 2020)
Information technology in the health sector is very important, especially to improve the quality of health services in hospitals. If the quality and service facilities at the hospital increase, so will the human soul that is helped. Information technology helps diagnose diseases, find the right medicine, find out various types of diseases, and analyze internal human organs that are difficult to see. Information technology in the form of Computerized Axial Tomography (CAT) System is useful for drawing the structure of parts of the brain and taking pictures of all immovable organs using X-rays. Dynamic Spatial Reconstructor (DSR) system that can be used to view images from various angles of the body's organs. Single Photon Emission Computer Tomography (SPECT), is a computer system that uses radioactive gas to detect body particles that are displayed in the form of images. Another form is Position Emission Tomography (PET) is also a computer system that can display images using radioactive isotopes. Besides Nuclear Magnetic Resonance is a diagnostic technique by magnetizing the nucleus (atomic center) of a hydrogen atom. DNA computer, which is able to diagnose disease while giving medicine.